Committees and special interests - Mike Felgenhauer; Hans Peter Grüner (European Central Bank (ECB), 2003)
Some committees convene behind closed doors while others publicly discuss issues and make their decisions. This paper studies the role of open and closed committee decision making in presence of external influence. We show that restricting the information of interest groups may reduce the bias towards special interest politics. Moreover, there are cases where benefits from increasing the number of decision makers can only be reaped if the committee's sessions are not public. In open committees benefits from voting insincerely accrue not only when a decision maker's vote is pivotal. As the number of voters increases, the cost of voting insincerely declines in an open committee because the probability of being pivotal declines. This is not the case in a closed committee where costs and benefits of insincere voting only arise when a voter is pivotal.
Keywords: D71; D72; D73; 330; Committees; common agency; interest groups; voting